Localization Operators and Scalogram Associated with the Deformed Hankel Wavelet Transform - Mejjaoli, Hatem; Trimèche, Khalifa (Mediterranean journal of mathematics, 2023)
The deformed Hankel wavelet transform (( k , n )-HWT) is a novel addition to the class of wavelet transforms, which has gained a respectable status in the realm of time-frequency signal analysis within a short span of time. Knowing the fact that the study of localization operators is both theoretically interesting and practically useful, we investigated several subjects of time-frequency analysis for the deformed Hankel wavelet transform. First, we study the L p boundedness and compactness of localization operators associated with the deformed Hankel wavelet transforms on R . Next, involving the reproducing kernel and spectral theories we investigate the time-frequency operators. Finally, the scalogram for the deformed Hankel wavelet transform is introduced and studied at the end.